„PRZYJAZNY CUDZOZIEMIEC”. UCIECZKA I DŁUGA DROGA ADOLFA BERGERA DO STANÓW ZJEDNOCZONYCH (1938-1942) - Jońca, Maciej (Zeszyty Prawnicze, 2016)
„A FRIENDLY ALIEN”. ADOLF BERGER’S ESCAPE AND A LONG WAY TO THE UNITED STATES (1938-1942) Summary Adolf Berger (1882-1962) belongs to the group of the most illustrious world romanists. Among his many eminent works one must not forget to quote the monumental “Encyclopedic Dictionary of Roman Law”. Berger was born in Lwów in a Jewish family. During his whole life he felt strong connections with Poland. This attitude found its most significant expression after the World War I. Despite his perfect knowledge of German and rich contacts in German speaking countries, Berger offered his services to the reborn Poland. Therefore from 1919 to 1938 he was working as a secretary and then as a legal advisor for the Polish Consulate in Vienna. During that time he did not ceased his research in the field of Roman law. Shortly after Anschluß he left Austria and moved to France and later to Italy. Escaping from the Nazis, he finally settled in New York where he found refuge and could resume his scientific work. His abandonment of Vienna and a long journey to the United States was possible only due to his Polish citizenship.